Experimental study on surface integrity in end milling of hastelloy c-2000 superalloy - Norhaida, Ab Razak; Md Mustafizur, Rahman; Kadirgama, Kumaran (Universiti Malaysia Pahang, 2014)
This paper presents an experimental study of surface integrity in end milling of Hastelloy C-2000. The experiment was carried out using two different cutting inserts under wet conditions – namely physical vapor deposition coated carbide with TiAlN and uncoated carbide. Design of experiment was implemented with a Box-Behnken design. The surface integrity of the workpiece was analyzed through scanning electron microscopy (SEM) and chemical element changes were inspected by an energy dispersive X-ray (EDX) test. The surface integrity of Hastelloy C-2000 was better when machining with coated carbide compared to uncoated carbide cutting inserts, mainly because the coating layer of coated carbide acted as a protecting layer to the cutting tool insert. Surface defects such as feed marks, surface tearing, plucking, cracking and adhered chips were found during the machining process. The chemical element changes happened due to the adhesion and diffusion mechanisms which were identified using SEM and EDX.